Epidemiology of depressive disorders among youth during Gaokao to college in China: results from Hunan Normal University mental health survey - Yang, Wenhui; Sun, Rui; Wang, Chong; Chen, Jie; Zhang, Chunguang; Yu, Jie; Liu, Haihong (BMC psychiatry, 2023)
Background Given the serious consequences of depression and the lack of information about it during the crucially developmental period from the National College Entrance Exam (CEE, i.e., Chinese gaokao ) to college, this study aimed to estimate the cumulative incidence, prevalence, age of onset, correlates, and service use of depressive disorders (DDs) among youth who passed the CEE and were enrolled at Hunan Normal University in China. Methods A two-stage cross-sectional epidemiological survey of DDs was conducted from October to December, 2017 among 6,922 incoming college students (98.5% effective response, N = 6,818, 71.4% female, age range: 16–25 years, mean age = 18.6). Using a stratified sampling method based on the risk of depression, 926 participants (mean age = 18.5, 75.2% female) were selected and subsequently interviewed with the Kiddie–Schedule for Affective Disorders and Schizophrenia–Present and lifetime version (K-SADS-PL). Results The sex-adjusted 9-month (i.e., 3 months pre-CEE, 3 months after CEE, and 3 months post-matriculation) incidence of new-onset DDs was 2.3% (standard error [S.E.] 0.3%), and the sex-adjusted 1-month, 6-month and lifetime prevalence were 0.7 (S.E. 0.3%), 1.7 (S.E. 0.2%) and 7.5% (S.E. 1.3%), respectively. The median age of onset was 17 (interquartile range: 16–18) years. Critically, over one-third (36.5%, S.E. 0.6) of depressed youth had their new onset during the 9-month period. The risk factors for depression included having mothers with higher education, experiencing major life events, being female, and experiencing parental divorce or death. The adjusted lifetime treatment rate was 8.7%. Conclusion The 9-month incidence of new-onset depression from gaokao to college among the youth sample in China is similar to the global annual incidence (3.0%), but the 1-month and lifetime prevalence are significantly lower than the global point (7.2%) and lifetime prevalence (19%). These findings suggest a high proportion of new-onset depression during the CEE to college among the sample youth in China. The risk of depression is associated with familial and stress correlates. Low treatment is a serious concern. Emphasis on early prevention and available treatment for adolescent and young adult depression is a critical need in China.